Design of 1-(furan-2-yl)-N-(5-substituted phenyl-1, 3, 4-thiadiazol-2-yl) methanimine derivatives as Enoyl-ACP reductase inhibitors: Synthesis, molecular docking studies and anti-tubercular activity - Bijo Mathew; Githa Elizabeth Mathew; George Sonia; Anila Kumar; Neethu P Charles; Palanisamy Kumar (Bangladesh Pharmacological Society, 2013)
A series of 5-phenylsubstiuted 1, 3, 4 thiadiazoles clubbed with furan moiety (Fa-Fe) by means of azomethine linkage have been synthesized. All the newly synthesized compounds were characterized by IR,1HNMR and Mass analyses. All the synthesized molecules have been predicted as anti-tubercular in nature by PASS in silico approach. In vitro anti-tubercular screening was performed by alamar blue assay method on Mycobacterium tuberculosis H37Rv strain. Among the synthesized derivatives Fb and Fe were active at 3.125 µg/mL against Mycobacterium tuberculosis H37Rv strain. The mechanism of action of the active compounds was carried out by docking of receptor enoyl-ACP reductase. It has been concluded that both Fb and Fe posses a significant interaction of hydrogen bonding and electrostatic attraction with Tyr 158 and Met103 in the active site of enzyme.